S100A10 and its binding partners in depression and antidepressant actions - Chen, Michelle X.; Oh, Yong-Seok; Kim, Yong (Frontiers in Molecular Neuroscience, 2022)
S100A10 (p11) is an emerging player in the neurobiology of depression and antidepressant actions. p11 was initially thought to be a modulator of serotonin receptor (5-HTR) trafficking and serotonergic transmission, though newly identified binding partners of p11 and neurobiological studies of these proteins have shed light on multifunctional roles for p11 in the regulation of glutamatergic transmission, calcium signaling and nuclear events related to chromatin remodeling, histone modification, and gene transcription. This review article focuses on direct binding partners of p11 in the brain including 5-HTRs, mGluR5, annexin A2, Ahnak, Smarca3, and Supt6h, as well as their roles in neuronal function, particularly in the context of depressive-like behavior as well as behavioral effects of antidepressant drug treatments in mice. In addition, we discuss neurobiological insights from recently uncovered p11 pathways in multiple types of neurons and non-neuronal cells and cast major remaining questions for future studies.